Plasma sCD14 as a biomarker to predict pulmonary exacerbations in cystic fibrosis. - Bradley S Quon; David A Ngan; Pearce G Wilcox; S F Paul Man; Don D Sin (PLoS ONE)
Background One in four cystic fibrosis (CF) patients diagnosed with a pulmonary exacerbation will not recover their baseline lung function despite standard treatment. This highlights the importance of preventing such events. Clinical decision-making can be improved through a simple blood test that predicts individuals at elevated short-term risk of an exacerbation. Methods We obtained plasma samples from 30 stable CF patients from the St. Paul's Hospital Adult CF Clinic (Vancouver, Canada). For 15 patients, an additional plasma sample was obtained during an exacerbation. Soluble CD14 (sCD14) and C-reactive protein (CRP) were quantified using ELISA kits. Myeloperoxidase (MPO), interleukin(IL)-6, IL-1β, monocyte chemoattractant protein-1 (MCP-1), vascular endothelial growth factor (VEGF), and granulocyte colony-stimulating factor (G-CSF) were quantified using Luminex™ immunoassays. Stable state biomarker levels were examined in their ability to predict individuals that would experience a pulmonary exacerbation requiring intravenous (IV) antibiotics within 4 months. Paired stable and exacerbation plasma biomarker levels were also compared. Results sCD14 levels were significantly higher in patients that experienced a pulmonary exacerbation requiring IV antibiotics within 4 months (p = 0.001). sCD14 cut-off value of 1450 ng/mL was associated with an area under the curve of 0.91 (95% CI 0.83-0.99) for predicting an exacerbation within 4 months of a stable visit, with a sensitivity of 100% and specificity of 82%. Plasma sCD14 levels were significantly higher during exacerbations than during periods of clinical stability (p = 0.03). Conclusions Plasma sCD14 is a promising biomarker for identifying CF patients who will exacerbate within 4 months of a stable visit but requires further study in larger, independent cohorts.